Hubungan Tingkat Stres dengan Kualitas Tidur pada Mahasiswa Tingkat Akhir di Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi - Clariska, Windi; Yuliana, Yuliana; Kamariyah, Kamariyah (Jurnal Ilmiah Ners Indonesia, 2020)
Internal and external obstacles that occur in final year students can cause students to be depressed and stressed and have an impact on the quality of their sleep. The results of the preliminary survey on 23 students found it difficult to rest since their thesis writing. WHO data for 2019, nearly 264 million people in the world experience stress and depression. To determine the relationship between stress levels and sleep quality in final year students at the Faculty of Medicine and Health Sciences, Jambi University. This research is a quantitative descriptive study on 92 samples of final year students at the Faculty of Medicine and Health Sciences, Jambi University using the method cluster random sampling. This study uses primary data obtained from questionnaires and data analysis using the Spearman rank test with p value = 0.05. 23 respondents (25%) experienced mild stress, 21 respondents (22.8%) moderate stress, 22 respondents (23.9%) severe stress and 5 very severe stress (5.4%). Poor sleep quality amounted to 84 respondents (91.3%) while good amounted to 8 respondents (8.7%). From the results of the Spearman Rank analysis, it was obtained a p-value of 0.030 with a closeness of the relationship of 0.227. There is a significant relationship between stress levels and sleep quality in final year students at the Faculty of Medicine and Health Sciences, Jambi University. Abstrak Hambatan internal dan eksternal yang terjadi pada mahasiswa tingkat akhir dapat menyebabkan mahasiswa tertekan dan stres serta berakibat pada kualitas tidurnya. Hasil survey pendahuluan pada 23 mahasiswa, merasa sulit beristirahat semenjak menjalani pembuatan skripsi. Data WHO tahun 2019 hampir 264 juta penduduk dunia mengalami stres dan depresi. Tujuan dari penelitian ini adalah mengetahui hubungan tingkat stres dengan kualitas tidur pada Mahasiswa tingkat akhir di Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi. Penelitian ini merupakan penelitian deskriptif kuantitatif pada 92 sampel mahasiswa tingkat akhir di Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi dengan metode cluster random sampling. Penelitian ini menggunakan data primer yang diperoleh dari kuesioner dan analisa data menggunakan uji spearman rank dengan p-value = 0,05. Didapatkan mahasiswa yang mengalami tingkat stres ringan 23 responden (25%), stres sedang 21 responden (22,8%), stres berat 22 responden (23,9%) dan stres sangat berat 5 responden (5,4%). Kualitas tidur buruk berjumlah 84 responden (91,3%) sedangkan baik berjumlah 8 responden (8,7%). Dari hasil analisis Spearman Rank didapatkan p-value 0,030 dengan keeratan hubungan 0,227. Terdapat hubungan yang bermakna antara tingkat stres dengan kualitas tidur pada mahasiswa tingkat akhir di Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi. Kata Kunci: Stres, Kualitas tidur, Mahasiswa.